A quantum-inspired approximate dynamic programming algorithm for unit commitment problems considering wind power - Hua Qin; Hua Wei (2017 IEEE International Conference on Smart Grid and Smart Cities (ICSGSC), 2017)
A quantum-inspired approximate dynamic programming algorithm (QI-ADP) is proposed for solving unit commitment problems considering wind power (WUC). The quantum computing theory is applied to tackle some new issues rising from ADP. In details, the unit states in a WUC problem are expressed by the quantum superposition. Then, the collapsing principle of quantum measurement is applied to solve the Bellman equation of ADP speedily. Based on the quantum rotation gate, the pre-decision states of the ADP are generated by quantum amplitude amplification technology. In the proposal algorithm, the quantum computation balances between state space exploration and exploitation automatically. Test cases of WUC are performed to verify the feasibility of the proposal approximate algorithm for the range of 10 to 100 units with 24-hour with ramp rate constraints. The experimental results show that the QI-ADP algorithm can find the sub-optimal solutions of large scale WUC problems within a reasonable time, and the average operational cost is reduced by 9.38% when the wind power is consumed. As a result, it is feasible to use the quantum computing theory to tackle some new issues rising from ADP, and the QI-ADP can be applied to solve large-scale WUC problems.